'Reflection is embedded in my brain forever now!': personal development as a core module on an Executive MBA. Issue 3 (4th May 2018) - Dalton, Chris
Abstract: Professional progression and skills development are the main expectations of mid-career managers when enrolling on an Executive MBA (EMBA), yet it can be personal development (PD) that turns out to be the unexpected benefit of management education. Joining a growing number of voices making a case for personal development and self-awareness in management education, and calling for schools to incorporate it in the curriculum, this paper advances the case for personal development as a core Executive MBA module. The paper sets out the holistic rationale and philosophic principles used to design and deliver a course underpinned by curiosity and self-reflection on an EMBA in the United Kingdom, and presents empirical findings from a survey conducted among 230 students and alumni. These suggest that the focus on reflective practice and integration of PD promotes a richer and deeper appreciation of the value of reflection for lasting and sometimes unexpected personal growth. In addition, the raising of awareness of self also brings awareness of others, and develops critical thinking in application of the MBA at work. The paper concludes with a discussion re-evaluating the subject of tacit knowledge in reflective practice.